INNV-19. NAVIGATING GLIOBLASTOMAS THE DIGITAL WAY: AN OBSERVATIONAL OVERVIEW OF THE USE OF A SMARTPHONE WEB APPLICATION IN A GBM PATIENT POPULATION. (12th November 2021) - Fine, Catherine; Brown, Jon; Tozour, Erin; Mason, Chris; Wels, Stephanie; Radick, Zack; Tucker, Simon; Bilstein, Alex; Gottlieb, Jordan; Lee, Tammy; Devitte, Ashley; Corbett, Kevan; et al.
Abstract: There is limited data regarding the use of digital resources in the neuro-oncology clinic, and more specifically within the glioblastoma (GBM) patient population. Studies show that smartphone applications are feasible as a resource to improve patient-reported outcomes, produce actionable provider data, and actively engage patients in their care, leading to patients being empowered in their choices, apt to adhere to recommendations and producing quality conversations with providers. Navio, an oncology digital health company, helps patients, providers, researchers, and industry collaborators by offering personalized treatment regimens, appointment reminders, help with medication use, diagnosis education, resources, and a means to record quality of life and patient-generated health data, which can be surfaced in real-time to oncology care teams. Seventy-seven patients with a GBM, ages 25-74 years, who were beginning or receiving treatment, were invited via SMS text to access the Navio web application. Nine different GBM treatment plans and 10 different countries were represented among the patients. Patients were allowed unlimited access to all modules and encouraged by text to re-engage, at Navio-defined key moments. Of the invited patients, 58 / 77 (75 %) successfully self-onboarded to Navio's app. Of the 58 patients onboarded, 77 % continued to engage with the application at various time points past day 1 and as far out as day 180. Engagement was seen across all age groups. Navio was able to re-engage 60 % of all patients who had 7 days of inactivity. Oncology digital resources, such as Navio's app, are of increasing interest to gather and surface real-time data, and support patients outside of traditional clinic visits. Although early, Navio's application represents a unique and expanding opportunity to engage and empower GBM patients, specifically during key treatment moments, to provide information for patients and their oncology care teams, and most importantly, to improve patient outcomes.